2016
DOI: 10.1016/j.socscimed.2015.11.044
|View full text |Cite
|
Sign up to set email alerts
|

Subjective socioeconomic status and health in cross-national comparison

Abstract: Research has established a robust association between subjective socioeconomic status (SES) and health outcomes, which holds over and above the associations between objective markers of SES and health. Furthermore, comparative research on health inequalities has shown considerable variation in the relationship between different objective markers of SES and health across countries. Drawing on data from 29 countries, we present the first crossnational study on the subjective SES-health relationship. For two heal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(115 citation statements)
references
References 51 publications
8
91
1
Order By: Relevance
“…In accord with recent research from several countries [24, 32, 35, 69], our findings demonstrate that lower SSS is associated with poorer mental health over and above the associations with objective SES measures. Such an independent association of SSS was previously found for depressive symptoms among adults in the U.S., England, and Hong Kong [7074].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accord with recent research from several countries [24, 32, 35, 69], our findings demonstrate that lower SSS is associated with poorer mental health over and above the associations with objective SES measures. Such an independent association of SSS was previously found for depressive symptoms among adults in the U.S., England, and Hong Kong [7074].…”
Section: Discussionsupporting
confidence: 92%
“…The current unemployment rate is at its lowest since German reunification [34]. Correspondingly, people in Germany rate their social standing higher than people in other European countries [35]. As objective socioeconomic factors substantially determine people’s perceptions of their social standing, which in turn can independently predict changes in mental health [36], we investigated whether SSS is a potential mediator of the association between objective SES and depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In previous literature, subjective SES is highly correlated with health even after controlling for objectively measured SES (Nobles et al 2013; Prag et al 2015). Thus, one explanation for the current study’s findings may be of reverse causation, in which individual’s assessment of their own SES is mediated by their health status or that both subjective status and health outcomes are affected by a common underlying variable (Garbarski 2010; Nobles et al 2013).…”
Section: Discussionmentioning
confidence: 84%
“…It has been shown to predict mortality and morbidity and has high test-retest reliability in a number of studies (Idler and Benyamini, 1997). Furthermore, this variable has been recommended by the World Health Organization for comparative research (De Bruin et al, 1996) and a large number of researchers have followed this advice Präg et al, 2016). Research has also shown that the associations between objective health indicators and self-perceived health are largely similar across countries (Bardage et al, 2005).…”
Section: Datamentioning
confidence: 99%